Housing Resources of Urban Areas of the Podkarpackie Province as a Competitive Advantage of the Region - Baran, Ewa; Grzebyk, Bogumiła (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The analysis of the collected scientific material has proved that housing resources of urban areas in the province of podkarpackie may become a significant factor for development of demographic potential in the migration processes especially among young people. This, in turn, results in competitive advantage of the region within the country and also the EU. The capital city of the region – Rzeszow is an example of a big city which has been increasing its population via migrations from rural areas within the province due to better working and living conditions. Despite existing depopulating cities such as Łódź or Poznań, there are in Poland such cities as Rzeszow or Warsaw which have become a magnet attracting new dwellers. This may be proved by remarkable increase in sales of new flats in the primary market and rising number of new flats to rent during the last few years. It should be noted that such a situation has been influenced by changes in economic factors, rise in remuneration in particular, decline in unemployment and the Gross Domestic Product greater than before. Demographic factors such as population growth, positive balance of migration and the number of marriages have become additional factors for certain cities and impacted positively on the demand in the housing market. Nevertheless, the noticeable phenomenon of depopulation and aging in communities in some urban areas in the province of podkarpackie does not pose a positive outlook for the future.